Adding CuCo2O4-GO to inhibit bromate formation and enhance sulfamethoxazole degradation during the ozone/peroxymonosulfate process: Efficiency and mechanism. (January 2022) - Liu, Zhao; Wang, Sibin; Ma, Weixing; Wang, Jingyi; Xu, Huining; Li, Kai; Huang, Tinglin; Ma, Jun; Wen, Gang
Abstract: In this work, a new type of catalyst CuCo2 O4 -GO was synthesized as a heterogeneous catalyst, and its control effect on bromate (BrO3 − )generation and sulfamethoxazole (SMX) degradation in O3 /PMS process was studied. When 100 mg/L CuCo2 O4 -GO was added to the reaction system, the BrO3 − concentration generated was 0.25 μM at pH = 7.0, 100 μM PMS addition and 1.30 mg/min ozone injection after 30 min reaction. Compared with the 6.58 μM BrO3 − produced in the control group, the addition of CuCo2 O4 -GO prominently inhibited the generation of BrO3 − and the inhibition efficiency reached 96.17 %. The addition of CuCo2 O4 -GO inhibited the conversion of hypobromous acid, thereby inhibiting the formation of BrO3 − . Meanwhile, the first-order kinetic constant of the degradation of SMX by O3 /PMS and O3 /PMS/CuCo2 O4 -GO was 0.163 and 0.422 min −1, respectively. The addition of CuCo2 O4 -GO promoted the degradation of SMX and the removal efficiency was reached above 98 % after 10 min reaction. According to the optimization of the GO loading ratio, it was found that CuCo2 O4 -GO with 20 % GO loading had the best promotion effect on the degradation of SMX, and almost completely inhibited the formation of BrO3 − . Finally, in the repeated cycle experiment, CuCo2 O4 -GO could maintain its high catalytic activity and still had a high removal effect on SMX after three repeated uses. Besides, the BrO3 − inhibition efficiency was above 80 % after two repeated uses. Therefore, adding synthetic CuCo2 O4 -GO is an effective way to control the formation of BrO3 − and enhance the degradation of SMX in the O3 /PMS process. Graphical abstract: Image 1 Highlights: CuCo2 O4 -GO could inhibit the formation of BrO3 − and enhance the degradation of SMX. CuCo2 O4 -GO could reduce HOBr/OBr − to form Br − and block BrO3 − formation. The optimal GO percentage of CuCo2 O4 -GO was determined to be 20 %. CuCo2 O4 -GO could maintain good performance after repeated use.